KAJIAN LOKASI POTENSIAL PENGEMBANGAN PERUMAHAN TERJANGKAU DI KOTA SEMARANG - Hajar Annisa Abdurahman; Iwan Rudiarto (Diponegoro University, 2017)
Human settlements supply has always been a problem in urban areas, particularly for the low-earners. There are few aspects to do in house procurement, such as location that will determine the cost of housing. Hence, this research aims to determine potential location to be developed as affordable housing for low-income people in Semarang. This research applied spatial analysis method based on Geographic Information System (GIS). The analysis results that only around 5,85% of allocated human settlement area in Semarang City is potential to be developed as affordable housing. In this study, the result show that in terms of location for affordable housing development, accessibility factor can determine the location with considering the particular planning standards.